The role of path length- and speed-related factors for the enhancement of section performance in alpine giant slalom - Spörri, J.; Kröll, J.; Schwameder, H.; Müller, E. (European Journal of Sport Science, 2018)
Knowing how to enhance alpine skiing performance is essential for effective coaching. The purpose of this study was to explore the role of path length- and speed-related factors for performance enhancement, while skiing on a homogeneously set/constantly inclined giant slalom course section (average gate distance: 27 m; offset: 8 m; slope inclination: 26°). During a video-based three-dimensional kinematic field-experiment, the data of six athletes who skied a two-gate section on four different types of skis were collected. The performance parameter analysed was section time. The performance predictors analysed were centre of mass (CoM), path length and the change in specific mechanical energy per entrance speed along the analysed section. Furthermore, since the current study examined alpine skiing performance within short sections, the skier`s entrance speed was also considered. Classified as a high-performance and a low-performance group based on section time, slow and fast trials significantly differed in CoM path length, the change in specific mechanical energy per entrance speed and entrance speed. The entrance speed of all trials analysed ranged between 15.25 and 17.66 m/s. In trials with both high and low entrance speed, the change in specific mechanical energy per entrance speed was found to be more relevant for the prediction of section time than CoM path length. However, further studies should investigate whether such a prioritization can be unrestrictedly generalized to other situations, such as entrance speeds, course sets, slope inclinations and competition disciplines different to those assessed in the current study.